2019
DOI: 10.1177/2041669519827974
|View full text |Cite|
|
Sign up to set email alerts
|

Asymmetries During Multiple Face Encoding: Increased Dwell Time and Number of Fixations in the Upper Visual Hemifield

Abstract: Visual field asymmetries in the encoding of groups of faces have rarely been investigated. Here, eye movements (percentage of dwell time [pDT] and number of fixations [nFix]) were recorded during the encoding of three groups of four faces tagged with cheating, cooperative, or neutral behaviours. Faces in each group were placed in the top left, top right, bottom left, or bottom right quadrants. Face recall was equally high in the three behavioural groups. Conversely, pDT and nFix were higher for faces in the up… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…The primary purpose of the present study was to examine whether daily exposure to the positional relationship between face and body influenced the emergence of the upper visual field bias for faces, which has been found in adults (Carlei et al, 2017;Fecteau et al, 2000;Felisberti & Currie, 2019;Felisberti & McDermott, 2013;Liu & Ioannides, 2010;Quek & Finkbeiner, 2014;Quek & Finkbeiner, 2016), by comparing the two age groups: 5-6 months as the less exposed group, and 7-8 months as the more exposed group. The results of Experiment 1 revealed that the upper visual field bias for faces was found in 7-to 8month-old, but not in 5-to 6-month-olds.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The primary purpose of the present study was to examine whether daily exposure to the positional relationship between face and body influenced the emergence of the upper visual field bias for faces, which has been found in adults (Carlei et al, 2017;Fecteau et al, 2000;Felisberti & Currie, 2019;Felisberti & McDermott, 2013;Liu & Ioannides, 2010;Quek & Finkbeiner, 2014;Quek & Finkbeiner, 2016), by comparing the two age groups: 5-6 months as the less exposed group, and 7-8 months as the more exposed group. The results of Experiment 1 revealed that the upper visual field bias for faces was found in 7-to 8month-old, but not in 5-to 6-month-olds.…”
Section: Discussionmentioning
confidence: 99%
“…© 2022 The Authors. Developmental Science published by John Wiley & Sons Ltd. et al, 2000;Felisberti & Currie, 2019;Felisberti & McDermott, 2013;Liu & Ioannides, 2010;Quek & Finkbeiner, 2014;Quek & Finkbeiner, 2016). Also, a visual illusion called "fat face illusion," in which a face in lower visual field is perceived bigger than that in upper visual field, has been reported (Rawal & Tseng, 2020;Sun et al, 2012Sun et al, , 2013.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although humans discriminate between human faces better than any other type of object (Werner, Kühnel, & Markowitsch, 2013), there are a number of other examples where facial-identity judgments are not immune to low-level influences. For example, there appears to be a relationship between facial processing and the location of a stimulus in an observer’s visual field, such that there is an advantage in facial processing in the upper visual fields compared to lower visual fields (Carlei, Framorando, Burra, & Kerzel, 2017; Felisberti & Currie, 2019; Felisberti & McDermott, 2013; Hagenbeck & Van Strien, 2002), and for faces processed centrally compared to in the periphery (Levy, Hasson, Avidan, Hendler, & Malach, 2001). The perceived gender of a face can even be biased by its visual field location (Afraz, Pashkam, & Cavanagh, 2010).…”
mentioning
confidence: 99%